Determinación de la calidad y fragilidad visual de los componentes de las unidades del paisaje del páramo en la Comuna la Libertad, Provincia de Cotopaxi propuesta de conservación, 2022. - Iza Chuquilla, Evelyn Paola (2022)
The present research project was developed with the objective of determining the quality and visual fragility of the components of the landscape units of the paramo of the Comuna la Libertad, located in the province of Cotopaxi. A methodology focused on the identification of landscape units, production systems based on the guidelines established by the Bureau of Land Management (BLM) method was used to determine visual quality, visual absorption quality (CAV) and consequently visual fragility. A mixed approach was established of qualitative values that were identified through photographs and quantitative values that allowed giving value to each of the criteria and components established for the visual evaluation of the landscape through the analysis of the registered photographs of the area under study. To obtain the photographs, field visits and surveys were generated to identify the different activities that take place on the site. As results, it was established that the paramo has a high visual quality of class A, where its areas present unique and outstanding features with an average of 19.75, the visual absorption capacity belongs to class II, presenting the fragility of the medium landscape with an average of 25.0 and a class II fragility with an average of 22.25, that is, the landscape has moderate fragility. It is concluded that there is a need to implement landscape conservation and management activities, being necessary to establish a conservation, regeneration and restoration plan for the area.